Obtenção de suco misto de açaí, morango e acerola em pó por diferentes processos de secagem - Rocha, Carolina Tatagiba da (2013)
The concern of the population in consume healthier foods has provided an increase in the consumption of fruit juices and the development of mixed juices has been characterized as a new trend. The sale of juice in powder form has advantages regarding chemical and microbiological stability. The present study aimed to develop a mixed powder juice of acai, strawberry and acerola using two drying processes: freeze-drying and hot air drying. Following the design of mixing centroid simplex, prepared a juice mixed with 10 different formulations, with açaí ranging between 10 and 80%, strawberry between 10 and 80% and acerola between 10 and 80%. The total of the three variables was maintained at 100%. The 10 formulations were evaluated for vitamin C content, total solids and sensory acceptability (color, flavor, consistency and overall impression). The selected formulation was the one with good acceptability and high ascorbic acid content. Next, we tested two types of emulsifiers (Emustab and Albumin) in four levels (2.5, 5, 7.5 and 10%) for the preparation of a foam from the pulp mixture in preselected proportions. The foams were tested for density and stability. The foam produced was dried in 7 temperatures (40, 45, 50, 55, 60, 65 and 70 ° C) and was selected as the optimum temperature for drying provided smaller loss of vitamin C. The mixture of pulp and foam were dried in conventional dryer and lyophilizer and the dried products obtained were evaluated for solubility and moisture balance. The juices reconstituted from powders from the different processes were compared with the fresh juice as the following characteristics: color coordinates (L *, a *, b *, C *, h *), titratable acidity, pH, soluble solids and percentage of vitamin C. The formulation containing 33.33% of each fruit pulp was considered the best. The foam made with 5% of albumin was used for the subsequent drying due to its low density and good stability. The temperature of 60 ° C resulted in lower losses of vitamin C during the foam mat. The powders obtained by two processes showed solubility average of 46.5%, considered low. The final moisture content was lower for the freeze-drying foam (3.25%). The freeze-drying process was more efficient for the preservation of the vitamin C than the process using hot air regardless of the addition of emulsifier. The color coordinates, titratable acidity, soluble solids and pH suffered minor variations depending on the type of process. The addition of emulsifier increased the pH and the content of soluble solids. In general, it can be concluded that it is possible to produce a powdered juice mix using freeze-drying or drying with hot air.